The world of Ito Jakuchu : - Yasuhiro, Sato (Japan Publishing Industry Foundation for Culture (JPIC), 2020)
The present book includes full-color illustrations of Jakuchu's lifework as well as other important paintings, arranged chronologically and accompanied by commentary from a variety of perspectives.